TRAINING MASTER STUDENTS TO MAKE TRANSLATOR’S MACRO-LEVEL DECISIONS - Merkulova, Svitlana (The Modern Higher Education Review, 2025)
Studies revealed in the article uncover challenges in organising training of master’s degree students in making professional decisions to achieve better results in translation practice. Professional Aspects of Translation is one of the fundamental disciplines to train future professionals in the area of Translation. To make a decision at a macro level or to plan the results of translation is one of the important competencies of a translator. Macro-level decision is based on the choice of a strategy or strategies, as well as perfect planning of the results, including customers’ choices. Challenges of making the right decision lie in a deep understanding of the translation theory, namely, the concept of strategy in translation, differentiation of strategies and techniques of translation and their implementation into practice. Pre-translation stage is very important in the process of translation as it includes text analysis that influences further translators’ decisions. Global and Local strategies are classics of translation decisions. Creative strategies give translators some freedom in rendering fiction, artistic and imaginative texts in different areas of personal activities. Mastering professional decisions in translation is a complicated process with many puzzles, and the right choice of educational methods and procedures leads to success. Examination of actual studies in translation, analysis of current experience on the basis of existing translations, combination of theoretical basics with best practices, brainstorming and individual translation decisions become necessary training elements in teaching modern successful translators, who meet trendy translation market needs.